Sistem Pendukung Keputusan Pembagian Kelas Unggulan Siswa Baru Menggunakan Metode Promethee Pada STM Raksana Medan - Junaidi (Yayasan Kita Menulis, 2021)
Education has a very decisive role, not only for the development and manifestation of individuals but also for the development of a nation and a state. The progress of a culture depends on how that culture recognizes, appreciates, and uses its human resources. This is closely related to the quality of education provided to members of the community. The word decision means choice, namely the choice of two or more possibilities. Decision making is hardly a choice between right and wrong but what often happens is a choice between